REACH for rubber goods and tyres - Copping Barry (European Rubber Journal, 2013)
The regime aims to promote their safe management, and to progressively replace the most dangerous substances with safer alternatives. REACH came into force on 1 june 2007 and places specific obligations on the tyre and rubber industries and other downstream users.
Keywords: Rubber goods; Tyre